PROMOTION OF SOCIAL PEACE AND DEVELOPMENT BY SOCIAL DESIGN - Fan, Kuo-Kuang; Chang, Chia-Lin (Journal of Dharma, 2021)
Through the process of action research, this study mainly discusses the way to help students think, interact, create, and reflect through the process of social design and comes up with creative ideas to promote social peace and development. In the teaching, teachers guide students to explore the problems connected with socialization and its impacts based on three aspects, i.e. diversified groups, sustainable community, and ethics. Besides, the issues related to peace and development behind such issues are put forward from the perspectives of critical thinking by taking students’ beliefs, attitudes, and values towards these issues into account. Finally, teachers assist students in cooperation and sharing through social design activities and propose ways to solve these problems from design thinking. In the teaching processes of “Social Design Action for Social Peace and Development,” we use eight meaningful methods and steps to help students establish more comprehensive values for social peace and development. It is expected to support students to rethink the current social situation and crisis and develop an attitude of peace promotion and cooperation in the learning process of social design, thereby realizing a sustainable and stable interaction on a social scale.